EKSISTENSI JALADWARA DALAM MEMBENTUK RUANG SAKRAL PADA SITUS PATIRTHAN PENINGGALAN KERAJAAN SINGHASARI: STUDI KASUS : SITUS PATIRTAN WATUGEDE SINGOSARI KABUPATEN MALANG - Yusran, Yusfan; Roro Rahmawati Tri , Wahyuni; Kusdiwanggo, Susilo (Studi Budaya Nusantara, 2024)
In Javanese cultural cosmology, particularly in Hindu-Buddhist beliefs, patirtan (sacred bathing) which generally has a spring source holds significant meaning. Since the era of Hindu kingdoms on the island of Java, the concept of water gardens as sacred bathing places known as patirtan has been recognized. However, unlike Hindu patirtan, the patirtan from the Singasari kingdom has its uniqueness due to the influence of both immigrant and local cultures, which can be seen in the spatial concepts and ornamentation of the patirtan. One of the important ornaments of this patirtan is the fountain statue, also known as Jaladwara, which makes it the strongest element among the others and simultaneously gives the patirtan a function beyond fulfilling daily water needs, as it is also used for religious rituals. The revelation of a Jaladwara serves as the focal point of this research, based on supporting data from archaeological findings at the Patirtan site, using the study object at the Patirtan Watugede site. This research aims to understand the forms of macro spatial arrangement, micro spatial arrangement, and the ornamentation of the Jaladwara at the Patirtan Watugede site. The macro space structure includes the cosmology of the patirtan, while the micro space structure encompasses the physical form of the patirtan. In addition, it also aims to describe the spatial role of Jaladwara in shaping sacred space in patirtan. This research employs a quasi-qualitative method to formulate findings that are descriptive and ideographic, using discourse analysis techniques on case objects from the perspective of the concept of space. The findings indicate that the location of Jaladwara influences the spatial arrangement patterns in the sacred area, which in turn impacts the circulation patterns within the region, especially for religious practitioners during ritual processes.